การควบคุมเมทริกซ์คอนเวอร์เตอร์บนฐานของวิธีเวนทูรินิ ภายใต้เงื่อนไขแรงดันอินพุตไม่ได้ดุล - ภรณ์พิมล บุญเสริม (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Matrix converters have been popularly applied for converting the three-phase ac voltage sources on the input side to the three-phase ac output voltages, as required. In fact, due to a high number of the switching devices (18 switches), a Venturini method is attractively regarded in this study to control the matrix converter based on the simplified implementation of the carrier-based pulse width modulation technique. Moreover, it can further provide the maximum magnitude of the output voltage compared with the other control methods. However, if the three-phase ac voltage sources are unbalanced, it will directly lead to the output voltage distortion of this converter. In this independent study, a control of the matrix converter based on Venturini method under unbalanced input voltage conditions is proposed. The aim of this research is to solve the impacts of the unbalanced input voltages on the matrix converter performance. Conceptually, this is done by emphasizing the analytical mathematic model for controlling the modulation based matrix converter, governing both single- and two- phase unbalanced input voltage conditions. Performance of the proposed control strategy was verified via the simplified simulation model in the MATLAB/Simulink software and also clearly evident that it is able to control the matrix converter for regulating the balanced output voltage and showing good steady-state operation.